2015
DOI: 10.1038/jp.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Standard methods based on last menstrual period dates misclassify and overestimate US preterm births

Abstract: Obstetric estimates provide the most clinically relevant estimates of US preterm births. Assessments calculated from LMP alone may overestimate prematurity incidence by ~20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The finding of the present study that LMP-based gestational age overestimated PTB when compared to ultrasonography-based gestational age corroborates population data in the USA [8,13]. Until recently, the National Center for Health Statistics and the Centers for Disease Control and Prevention (CDC) in the USA-based national estimates of PTB on LMP dating, the sole determinant of gestational age at delivery on birth certificates in many states.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The finding of the present study that LMP-based gestational age overestimated PTB when compared to ultrasonography-based gestational age corroborates population data in the USA [8,13]. Until recently, the National Center for Health Statistics and the Centers for Disease Control and Prevention (CDC) in the USA-based national estimates of PTB on LMP dating, the sole determinant of gestational age at delivery on birth certificates in many states.…”
Section: Discussionsupporting
confidence: 88%
“…In a report that explained the rationale for this shift, the CDC demonstrated that the PTB rate in 2013 was 11.39% based on LMP alone, compared to 9.62% based on the best obstetric estimate [13]. Another study using data from the USA reported a similar difference in PTB rates based on LMP alone compared to obstetric estimate in 2012 [8]. The authors also demonstrated that two objective indicators of clinical prematurity—NICU admission and low birth weight —correlated more closely with the obstetric estimates of gestational age at delivery than with LMP dating [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Centers for Disease Control natality statistics regarding the incidence of preterm births and published estimates of the prevalence of hemodynamically significant congenital heart disease among children 12–23 months of age, these aforementioned populations cumulatively represent approximately 0.77% of US children <24 months of age (Table 1 ). 2 5 …”
Section: To the Editorsmentioning
confidence: 99%
“… 1 There are limitations in the COID's use of NVSN data to describe a small subset of the population, such as preterm infants <35 or <32 wGA who only comprise 4% and 1.6% of all births, respectively. 3 Because palivizumab reduces RSV hospitalization in preterm infants, 4,5 it is also necessary to understand the proportion of infants receiving palivizumab when assessing RSV hospitalization rates in these infants.…”
Section: Introductionmentioning
confidence: 99%